2019
DOI: 10.1101/19000281
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LncRNA and predictive model to improve the diagnosis of clinically diagnosed pulmonary tuberculosis

Abstract: Background: Clinically diagnosed pulmonary tuberculosis (PTB) patients lack Mycobacterium tuberculosis (MTB) microbiologic evidence, and misdiagnosis or delayed diagnosis often occurs as a consequence. We investigated the potential of lncRNAs and corresponding predictive models to diagnose these patients. Methods: We enrolled 1372 subjects, including clinically diagnosed PTB patients, non-TB disease controls and healthy controls, in three cohorts (Screening, Selection and Validation). Candidate lncRNAs differe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Hu et al. ( 183 ) have shown that three lncRNAs, ENST00000497872, n333737, and n335265 are differentially expressed in blood samples of active TB patients compared to healthy individuals and suggested that these may serve as potential biomarkers for clinically diagnosed PTB patients. Of these, lncRNA ENST00000497872 is located close to the immune related gene immunoglobulin heavy constant alfa 1 (IGHA1) and n333737 is located close to the immune related gene T cell receptor alfa variable 1-2 (TRAV1-2).…”
Section: Non-coding Rnas As Markers Of Active Tb and Ltbimentioning
confidence: 99%
“…Hu et al. ( 183 ) have shown that three lncRNAs, ENST00000497872, n333737, and n335265 are differentially expressed in blood samples of active TB patients compared to healthy individuals and suggested that these may serve as potential biomarkers for clinically diagnosed PTB patients. Of these, lncRNA ENST00000497872 is located close to the immune related gene immunoglobulin heavy constant alfa 1 (IGHA1) and n333737 is located close to the immune related gene T cell receptor alfa variable 1-2 (TRAV1-2).…”
Section: Non-coding Rnas As Markers Of Active Tb and Ltbimentioning
confidence: 99%
“…Compelling studies have proposed that models incorporating biomarkers and EHR information attain better performance for prediction of sepsis 17 and abdominal aortic aneurysm 18 . We previously reported that combining exosomal microRNAs and EHRs in the diagnosis of tuberculous meningitis (TBM) achieved AUCs of up to 0.97 versus an AUC of 0.67 obtained using EHR alone 19 . Based on these studies, we hypothesized that combining lncRNAs with well-defined EHR predictors could be used to develop improved predictive models to identify PTB cases that lack microbiologic evidence of MTB infection.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] However, these approaches have various drawbacks, including the time delay for positive culture and poor sensitivity (20%–60%) of microscopy. [ 7 , 8 ] The Xpert MTB/RIF assay is recommended by the World Health Organization for the diagnosis of PTB. [ 9 ] However, this method is costly and limited in smear-negative sputum, especially in HIV-coinfected cases.…”
Section: Introductionmentioning
confidence: 99%